PENGOLAHAN PUPUK ORGANIK CAIR LIMBAH RUMAH POTONG HEWAN UNTUK KELOMPOK TANI KARYA USAHA II KABUPATEN KUBU RAYA - Dian Rahayu Jati (Jurnal Buletin Al-Ribaath, 2018)
ABSTRACTKarya Usaha II Farmer Group is still applying conventional farming systems which mean still very dependent on an-organic fertilizer. Excessive use of an-organic fertilizers will adversely affect the environment. Alternative solutions are made in the form of using organic fertilizers from local resources, namely cowhide blood waste. The implementation method used in this activity is participatory and collaborative methods. The success of this activity by using the participatory method is very much determined by the direct involvement of the community starting from the planning, fertilizer making, planting, fertilizing and maintenance processes. The results of this activity are expected to increase the independence of the farmer group partners in providing organic fertilizer for agricultural purposes as well as being able to initiate changes from conventional farming systems to organic farming systems. Keywords: Liquid Organic Fertilizer, Rice Farming, Waste of Cow Blood